Associations of dietary fiber intake with chronic inflammatory airway diseases and mortality in adults: a population-based study - Lin, Shanhong; Zhu, Ning; Zhang, Shengmin (Frontiers in Public Health, 2023)
Objective The objective of this study was to investigate the potential association between dietary fiber intakes and the prevalence of chronic inflammatory airway diseases (CIAD), as well as mortality in participants with CIAD. Methods Data was collected from the National Health and Nutrition Examination Survey (NHANES) 2013–2018, with dietary fiber intakes being calculated as the average of two 24-h dietary reviews and divided into four groups. CIAD included self-reported asthma, chronic bronchitis, and chronic obstructive pulmonary disease (COPD). Through December 31, 2019, mortality was identified from the National Death Index. In cross-sectional studies, multiple logistic regressions were used to assess dietary fiber intakes associated with the prevalence of total and specific CIAD. Dose–response relationships were tested using restricted cubic spline regression. In prospective cohort studies, cumulative survival rates were calculated using the Kaplan–Meier method and compared using log-rank tests. Multiple COX regressions were used to assess dietary fiber intakes associated with mortality in participants with CIAD. Results A total of 12,276 adults were included in this analysis. The participants had a mean age of 50.70 ± 17.4 years and was 47.2% male. The prevalence of CIAD, asthma, chronic bronchitis, and COPD were 20.1, 15.2, 6.3, and 4.2%, respectively. The median daily consumption of dietary fiber was 15.1 [IQR 10.5, 21.1] g. After adjusting for all confounding factors, linear and negative associations were observed between dietary fiber intakes and the prevalence of total CIAD (OR = 0.68 [0.58–0.80]), asthma (OR = 0.71 [0.60–0.85]), chronic bronchitis (OR = 0.57 [0.43–0.74]) and COPD (OR = 0.51 [0.34–0.74]). In addition, the fourth quartile of dietary fiber intake levels remained significantly associated with a decreased risk of all-cause mortality (HR = 0.47 [0.26–0.83]) compared to the first quartile. Conclusion Dietary fiber intakes were found to be correlated with the prevalence of CIAD, and higher dietary fiber intakes were associated with a reduced mortality in participants with CIAD.